Diversity of rotavirus strains causing diarrhea in <5 years old Chinese children: a systematic review. - Yue Li; Song-Mei Wang; Shan-Shan Zhen; Ying Chen; Wei Deng; Paul E Kilgore; Xuan-Yi Wang (PLoS ONE, 2014)
Background We conducted a systematic review of the diversity and fluctuation of group A rotavirus strains circulating in China. Methods and findings Studies of rotavirus-based diarrhea among children less than 5 years, published in English or Chinese between 1994 and 2012, were searched in PubMed, SinoMed, and CNKI and reviewed by applying standardized algorithms. The temporal and spatial trends of genotyping and serotyping were analyzed using a random-effects model. Ninety-three studies met the inclusion/exclusion criteria and were included in the meta-analysis. Overall, 22,112 and 10,660 rotavirus samples had been examined for G and P types, respectively. The most common G types were G1 (39·5%), G3 (35·6%), G2 (1·3%), and G9 (0·1%). Among P types, P[8] (54·6%) was the predominant type, followed by P[4] (11·1%) and P6 (0·1%). The most common G-P combinations were G3P[8] (32·1%) and G1P[8] (24·5%), followed by G2P[6] (13·2%) and G2P[4] (10·1%). Before 2000, serotype G1 was the predominant strain and accounted for 74·3% of all rotavirus infections; however, since 2000, G3 (45·2%) has been the predominant strain. Rotavirus P types showed little variation over the study period. Conclusion Despite the variation of serotypes observed in China, the G1, G2, G3, and G4 serotypes accounted for most rotavirus strains in recent decades. These results suggest that Chinese children will be adequately protected with currently available or forthcoming rotavirus vaccines.